IMPLEMENTASI MANAJEMEN BANDWIDTH METODE PCQ DAN QUEUE TREE DI PT KURNIA SYLVA - Zidan Rizaldi Naufal; Herman Kuswanto (University of Muhammadiyah Tangerang, 2026)
PT Kurnia SylvaÂ is a mapping consultancy company that heavily relies on internet connectivity to support its operations, especially within the Geographic Information System (GIS) division. However, the existing network infrastructure faces significant issues due to the absence of a bandwidth management system, resulting in uneven internet speed distribution across divisions. This study aims to implement an effective bandwidth management strategy using the Per connection queue (PCQ) and Queue tree methods on Mikrotik devices. The PCQ method is employed to automatically and fairly allocate bandwidth to each user within a division, while the Queue tree method is used to separate and manage bandwidth allocation based on traffic types, such as download traffic. The research methodology includes observation, interviews, literature review, network design, as well as simulation and testing using VirtualBox and WinBox. The test results indicate that the system successfully distributes bandwidth according to the predefined allocation for each division under both multi-user and multi-profile scenarios. The combination of PCQ and Queue tree methods has proven to be effective in achieving fair and efficient internet distribution, thereby improving overall network performance. This solution is deemed feasible for real-world implementation to support work productivity within PT Kurnia Sylva.